2011
DOI: 10.1063/1.3600343
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies of the tunneling splitting of malonaldehyde using the multiconfiguration time-dependent Hartree approach

Abstract: Full dimensional multi-configuration time-dependent Hartree calculations of the zero point energy and the tunneling splitting of malonaldehyde using a recently published potential energy surface [Y. Wang, B. J. Braams, J. M. Bowman, S. Carter, and D. P. Tew, J. Chem. Phys. 128, 224314 (2008)] are reported. The potential energy surface has been approximated by a modified version of the n-mode representation and careful convergence check has been performed to ensure accurate results. The obtained value for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 51 publications
4
96
0
Order By: Relevance
“…Additional convergence calculations are performed based on extrapolation schemes proposed recently. 48,49 The idea is to carry out a reference calculation by employing a small set of SPFs, and in turn by doubling the number of SPFs in each mode independently to calculate the energy difference with respect to the reference one. At the end the sum of all these differences is added to the reference energy to estimate its extrapolated value.…”
Section: Zero-point Energy and Ground-state Propertiesmentioning
confidence: 99%
“…Additional convergence calculations are performed based on extrapolation schemes proposed recently. 48,49 The idea is to carry out a reference calculation by employing a small set of SPFs, and in turn by doubling the number of SPFs in each mode independently to calculate the energy difference with respect to the reference one. At the end the sum of all these differences is added to the reference energy to estimate its extrapolated value.…”
Section: Zero-point Energy and Ground-state Propertiesmentioning
confidence: 99%
“…[4], we derived the conditions that vibrational conical intersections occur and presented quantum-dynamical model calculations to show the consequences for the vibrational dynamics and spectra. As a first simple example, we considered malonaldehyde which is a prototype molecule with a medium strong intramolecular hydrogen bond [10,[12][13][14][15][16]. We showed that a conical intersection exists between the first excited states of the OH stretch and the OH bend modes, respectively, which might provide an explanation for the ultrafast (a few 100 fs) vibrational relaxation and the complex oscillatory features found in infrared time-resolved pump-probe experiments for this type of molecular systems [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…4a). Its tunnel-splitting and intramolecular hydrogen-bond transfer has been studied extensively [14,[29][30][31][32], while we concentrate here on the dynamics within one of the potential energy wells. We treated the molecule on the MP2/6-311++g(2df,2pd) quantum-chemical level of theory, using the Gaussian program package [33].…”
mentioning
confidence: 99%